Penerapan pembelajaran berdiferensiasi dalam meningkatkan kemampuan bahasa Arab pada siswa madrasah aliyah negeri 2 Sragen - Yudo Zulkarnain; Mulyanto Abdullah Khoir (At Turots: Jurnal Pendidikan Islam, 2023)
This research aims to enhance the Arabic language proficiency of students at Madrasah Aliyah Negeri 2 Sragen through the implementation of differentiated learning. The methodology employed is Classroom Action Research, comprising four cyclic components: planning, action implementation, observation, reflection, and revision. The study consists of two cycles, each involving three 35-minute sessions. Data were gathered via observations, tests, and interviews from a sample of 31 10th-grade students at Madrasah Aliyah Negeri 2 Sragen, all with a 100% attendance rate. During the pre-cycle phase, 9 students (29.03%) achieved the Minimum Mastery Criteria (KKM), while 22 students (70.97%) did not, with an average score of 53.71. Following the first cycle, the number of students meeting the KKM increased to 13 (41.94%), and 18 students (58.06%) did not, with an average score of 71.06. In the second cycle, all 31 students (100%) met the KKM, with an average score of 82.13. The classical observation results indicated that kinesthetic ability reached 70%, with an average score of 3.5, auditory ability reached 50%, with an average score of 2.5, and visual ability reached 90%, with an average score of 4.5.